1995
DOI: 10.1590/s0004-282x1995000200014
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical rhythmic electrographic discharge in adults: an atypical evolution

Abstract: SUMMARY -The subclinical rhythmic electrographic discharge in adults (SREDA) has been rarely reported. We describe the case of a 71 year-old man with transient ischemic attack, whose EEG showed an atypical evolution of this uncommon pattern. The computed tomography scan and cerebrospinal fluid were normal. We are not aware of any other report in the literature with this atypical evolution of SREDA.KEY WORDS: subclinical rhythmic electrographic discharge in adults (SREDA), EEG. Descarga eletrográfica rítmica su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
5
0
2
Order By: Relevance
“…Few others have also reported SREDA in patients who had transient ischemic attack (TIA), transient global amnesia (TGA), and cerebellar degeneration. 7,8,12 These anecdotal reports shed some light on the possible pathogenesis of SREDA, but it still needs to be ascertained prospectively in a larger sample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Few others have also reported SREDA in patients who had transient ischemic attack (TIA), transient global amnesia (TGA), and cerebellar degeneration. 7,8,12 These anecdotal reports shed some light on the possible pathogenesis of SREDA, but it still needs to be ascertained prospectively in a larger sample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The causative mechanism of SREDA remains to be elucidated. Previous reports have suggested that the generation of SREDA is related to cerebrovascular disorders, ischemia, and transient hypoxia 1,4,9 . However, other reports do not supported these hypotheses 2,5 .…”
Section: Introductionmentioning
confidence: 93%
“…It is usually predominant over the parietal and temporal regions and lasts between a few seconds and a minute without any clinical manifestations or symptoms 2 . The prevalence of SREDA has been reported to be extremely small (0.002–0.045) 3 and SREDA is sometimes described as ‘subclinical’, 2,3 with some reports indicating that there is no correlation between SREDA and any specific clinical symptoms 4–6 . In addition, SREDA has been described most commonly in middle‐aged and elderly adults (over 40 years of age), 2,3,5,7 although SREDA has also been reported in children 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Temos também as pontas positivas 6/ 14 Hz, o "SREDA" (Fig. 12) 30 , que pode ser confundido com crise eletrográfica, a descarga rítmica temporal média, a pseudo-ponta-onda (hipersincronia hipnagógica), o ritmo da fenda em pacientes craniotomizados e mais recentemente o potencial "N" 31 . No caso de dúvida entre a atividade epileptiforme e a VB, a primeira geralmente fica mais freqüente conforme o sono vai aprofundando, enquanto a VB só aparece durante a sonolência 32 .…”
Section: Variantes Benignas Do Eegunclassified